Pengenalan Pola pada Anak Usia Dini: Rancangan Tugas dan Aktivitas Pendukung - Baiq Rofina Arvy (Journal on Education, 2023)
Pattern recognition in early childhood contributes to children's mathematical development at the next level of education. To maximize children's ability to recognize patterns, task plans and supporting activities are needed in early childhood learning activities. The purpose of this literature review is to explain the design of tasks and activities that educators can apply to develop children's abilities related to patterns in pre-mathematics. The research method used is literature study or literature review. This method collects library data obtained from books and articles in journals related to the concept of patterns in early childhood. The research results show that task designs that can develop educators include copying and making patterns, expanding patterns, translating patterns, identifying the smallest units in patterns, recognizing similar patterns and adding missing patterns. The supporting activities that can be implemented include ronce activities, playing letter cards and playing with blocks.